Breathing mode influence on craniofacial development and head posture - Annel Chambi-Rocha; Ma Eugenia Cabrera-Domínguez; Antonia Domínguez-Reyes (Elsevier, 2018)
Objective: The incidence of abnormal breathing and its consequences on craniofacial development is increasing, and is not limited to children with adenoid faces. The objective of this study was to evaluate the cephalometric differences in craniofacial structures and head posture between nasal breathing and oral breathing children and teenagers with a normal facial growth pattern. Method: Ninety-eight 7-16 year-old patients with a normal facial growth pattern were clinically and radiographically evaluated. They were classified as either nasal breathing or oral breathing patients according to the predominant mode of breathing through clinical and historical evaluation, and breathing respiratory rate predomination as quantified by an airflow sensor. They were divided in two age groups (G1: 7-9) (G2: 10-16) to account for normal age-related facial growth. Results: Oral breathing children (8.0 ± 0.7 years) showed less nasopharyngeal cross-sectional dimension (MPP) (p = 0.030), whereas other structures were similar to their nasal breathing counterparts (7.6 ± 0.9 years). However, oral breathing teenagers (12.3 ± 2.0 years) exhibited a greater palate length (ANS-PNS) (p = 0.049), a higher vertical dimension in the lower anterior face (Xi-ANS-Pm) (p = 0.015), and a lower position of the hyoid bone with respect to the mandibular plane (H-MP) (p = 0.017) than their nasal breathing counterparts (12.5 ± 1.9 years). No statistically significant differences were found in head posture. Conclusion: Even in individuals with a normal facial growth pattern, when compared with nasal breathing individuals, oral breathing children present differences in airway dimensions. Among adolescents, these dissimilarities include structures in the facial development and hyoid bone position. Resumo: Objetivo: A incidência da respiração anormal e de suas consequências no desenvolvimento craniofacial aumenta e não é limitada a crianças com fácies adenoideanas. O objetivo deste estudo foi avaliar as diferenças cefalométricas nas estruturas craniofaciais e na postura da cabeça entre crianças e adolescentes com respiração nasal e respiração bucal com padrão de crescimento facial normal. Método: 98 pacientes com idades entre 7-16 anos com padrão de crescimento facial normal foram avaliados de forma clínica e radiológica. Eles foram classificados como pacientes com respiração nasal ou respiração bucal de acordo com a predominância do modo de respiração por meio da avaliação clínica e histórica e da predominância da frequência respiratória conforme qualificado por um sensor de fluxo de ar. Os pacientes foram divididos em duas faixas etárias (G1: 7 a 9) (G2: 10 a 16) para contabilizar o crescimento normal facial relacionado à idade. Resultados: As crianças com respiração bucal (8,0 ± 0,7 anos de idade) mostraram menor dimensão transversal nasofaríngea (MPP) (p = 0,030), ao passo que outras estruturas foram semelhantes a seus pares com respiração nasal (7,6 ± 0,9 anos de idade). Contudo, os adolescentes com respiração bucal (12,3 ± 2,0 anos de idade) mostraram maior comprimento do palato (espinha nasal anterior-espinha nasal posterior (ENA-ENP)) (p = 0,049), maior dimensão vertical na menor face anterior (Xi-ENA-Pm) (p = 0,015) e menor posição do osso hioide a respeito do plano mandibular (H-PM) (p = 0,017) que seus pares com respiração nasal (12,5 ± 1,9 anos de idade). Não foram constatadas diferenças estatisticamente significativas na postura da cabeça. Conclusão: Mesmo em indivíduos com padrão de crescimento facial normal, em comparação a indivíduos com respiração nasal, as crianças com respiração bucal apresentam diferenças nas dimensões das vias aéreas. Entre os adolescentes, essas dissimilaridades incluem estruturas no desenvolvimento facial e na posição do osso hioide. Keywords: Breathing, Craniofacial development, Head posture, Children, Palavras-chave: Respiração, Desenvolvimento craniofacial, Postura da cabeça, Crianças